Smoking Behavior in National Health Insurance (JKN) Participants Recipients of Contribution Assistance (PBI) in Tenggela Village - Suci; Herlina; Yasir (Universitas Muhammadiyah Palu, 2026)
Smoking behavior is seen from various points of view as very detrimental, both for oneself and the people around him. Gorontalo Province is one of the provinces with the most smokers in Indonesia. The purpose of the study was to analyze factors related to smoking behavior in national health insurance (JKN) participants receiving contribution assistance (PBI) in Tenggela Village. Analytical observational research method with cross sectional design. The population in this study is the Heads of Families Participating in the National Health Insurance (JKN) Recipients of Contribution Assistance (PBI) in Tenggela Village as many as 638 Heads of Families. The sample in this study amounted to 246 families participating in Contribution Assistance Recipients (PBI) and used the Proportional Simple Random Sampling technique. Data collection by interviewing respondents using questionnaires and data was analyzed by chi square test. The results of the study showed that there was a relationship between age, occupation, knowledge, and expenditure with smoking behavior. Age produces p-value=0.000, work produces p-value=0.025, knowledge produces p-value=0.034, expenditure produces p-value=0.000. And there was no relationship between education and smoking behavior which resulted in p-value = 0.473. It is hoped that the local government will further socialize, realize, and evaluate the Smoke-Free Zone (KTR) policy in Tenggela village. And it is necessary to make binding rules and sanctions for the No Smoking Area policy.